Cave millipeds of the United States. V. The genus Idagona Buckett & Gardner (Chordeumatida, Conotylidae, Idagoninae) - Shear, William A. (Zootaxa, 2007)
The conotylid milliped subfamily Idagoninae presently includes but a single genus and species, Idagona westcotti Buckett & Gardner, known from lava tubes in Idaho, USA. This study presents new records of the genus Idagona, extending its distribution into Utah and Nevada, its habitat records to limestone caves, and describes two additional species, Idagona lehmanensis, n. sp., from limestone caves in the Great Basin National Park in eastern Nevada, and Idagona jasperi, n. sp., from a high-altitude limestone cave in northern Utah.